2022
DOI: 10.3389/fnins.2022.914894
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Voxel-Based Degree Centrality in Patients With Postpartum Depression: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Postpartum depression (PPD) is a major public health concern with significant consequences for mothers, their children, and their families. However, less is known about its underlying neuropathological mechanisms. The voxel-based degree centrality (DC) analysis approach provides a new perspective for exploring the intrinsic dysconnectivity pattern of whole-brain functional networks of PPD. Twenty-nine patients with PPD and thirty healthy postpartum women were enrolled and received resting-state functional magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Furthermore, there are abundant insulin receptors [83] in the hippocampus, and the activated insulin receptors may modulate the sensitivity of the reward system and memory function [84], thus influencing cognitive function and emotional regulation. Moreover, previous research also confirmed that the elevated DC values of the hippocampus existed in patients with the major depressive disorder [85,86], early-onset T2DM [31], post-stroke cognitive impairment [87], and subjective memory complaints [88], which were consistent with our results. In the present study, abnormal DC values of the hippocampus in depressed T2DM were negatively correlated with orientation score, which further supported the speculation that the hippocampus might be a susceptible brain region and involved in the cognitive impairment of T2DM patients.…”
Section: Abnormal Spontaneoussupporting
confidence: 92%
“…Furthermore, there are abundant insulin receptors [83] in the hippocampus, and the activated insulin receptors may modulate the sensitivity of the reward system and memory function [84], thus influencing cognitive function and emotional regulation. Moreover, previous research also confirmed that the elevated DC values of the hippocampus existed in patients with the major depressive disorder [85,86], early-onset T2DM [31], post-stroke cognitive impairment [87], and subjective memory complaints [88], which were consistent with our results. In the present study, abnormal DC values of the hippocampus in depressed T2DM were negatively correlated with orientation score, which further supported the speculation that the hippocampus might be a susceptible brain region and involved in the cognitive impairment of T2DM patients.…”
Section: Abnormal Spontaneoussupporting
confidence: 92%
“…The OFC is a critical brain region for emotion regulation and plays a significant role in maintaining reward, emotional states online, and decision-making (Du et al, 2020 ). Multiple studies found that OFC is an indispensable brain region associated with emotions, especially depression (Rolls et al, 2020 ; Zhang S. et al, 2022 ). A previous study found that disrupted functional interhemispheric connectivity between bilateral OFC may be related to the vulnerability of decision-making in PPD patients (Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A surface-based morphometry (SBM) study found that PPD patients showed a thinner cortical thickness in the right inferior parietal lobule compared with the healthy controls and increased surface area was observed in the left superior frontal gyrus, caudal middle frontal gyrus, middle temporal gyrus, insula, and right supramarginal cortex in PPD patients (Li et al, 2021 ), and a voxel-based morphometry (VBM) study found that PPD patients had increased regional gray matter volume (GMV) in the left dorsolateral prefrontal cortex (DLPFC.L) and right anterior insula (anI) relative to HPW (Cheng B. et al, 2022 ). Additionally, some functional magnetic resonance imaging (fMRI) studies have revealed that PPD patients exhibit altered neural function in brain networks involved in default mode network (DMN), salience network (SN), executive control network (ECN), sensorimotor network (SMN), reward network, and limbic system (LIN), which involved the DLPFC, anterior/posterior cingulate cortex (ACC/PCC), orbitofrontal cortex (OFC), medial prefrontal cortex, amygdala, hippocampus, temporal cortices, insular, striatum, middle frontal gyrus (MFG) and may underlie the deficits in cognitive control, emotional regulation, affective processing, reward processing, and visuospatial and body-signal integration (Mao et al, 2020 ; Zhang et al, 2020 ; Cheng et al, 2022 ; Zhang S. et al, 2022 ). However, most of these studies of PPD have focused on either structural or functional changes rather than both.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the FCD provides an unbiased search of functional connectome abnormalities within the whole brain without prior hypothesis [8]. This method has been used to detect functional reorganization patterns across diverse diseases, such as stroke [2,9,10], depression [11], and Parkinson's disease [12].…”
Section: Introductionmentioning
confidence: 99%